Onstraints towards the intention for sustaining engagement as an environmental volunteer - Alya Nasuha Abdul Rahman; Norshariani Abd Rahman; Shamsul Azhar Yahya (Penerbit Universiti Kebangsaan Malaysia, 2023)
Environmental volunteerism contributes to large-scale environmental conservation efforts. However, the constraints faced by volunteers have hindered the volunteers’ intention to continue their environmental volunteer engagement. Thus, this study examined the constraints and recommendations to sustain environmental volunteers’ involvement from the perspective of university students. This quantitative study employed the survey design. The questionnaire was distributed to 357 respondents who participated in environmental volunteering activities. The results showed that the constraints, recommendations and intention to sustain engagement as an environmental volunteer were at a high level. Both male and female volunteers experienced the same level of constraints. In terms of increasing environmental volunteer activities, female volunteers needed more support from the organization than male volunteers. The findings showed that female volunteers have had a higher intention to continue their involvement as environmental volunteers compared to men. In addition, there were significant differences between environmental volunteers from different categories of volunteerism in terms of constraints, suggestions and intention to continue their involvement as environmental volunteers. Therefore, the organizers of volunteer activities need to overcome the constraints faced by environmental volunteers by increasing social support, dissemination of information and emotional management to sustain the involvement of university students in environmental volunteering activities.